Toward a Secure and Stable Mali Approaches to Engaging Local Actors - Stephanie, Pezard (RAND Corporation, 2013)
Discusses how lasting security and stability can be established in northern Mali after the 2012 conflict there, with an emphasis on understanding the different groups that have been involved in the crisis, the drivers of conflict in northern Mali, and how historical examples can offer insights into how to engage local actors in security solutions.